The Polymorphism of rs2549782 gene Endoplasmic Reticulum aminopeptidase-2, high Concentration of Free Fetal DNA, and Cystatin C as Risk Factors of Preeclampsia - I Nyoman Hariyasa Sanjaya (Journal of Global Pharma Technology, 2016)
Background: Recently, the mechanism of the preeclampsia (PE) occurrence has not gained widespread agreement. This is related to the variations intreatment, maternal factor, and fetal morbidities as well as mortality. However, the studies of the placenta associated with PE mechanism have derived serious attention. This study aims to determine the role of rs2549782 ERAP 2 gene polymorphism, extracellular fetal DNA content, and high-level C cystatin in maternal serum as a risk factor for PE Methods: A matched case-control study among 62 maternal over 20 weeks of gestation was conducted in the Department of Obstetrics and Gynecology, Faculty of Medicine, Sanglah General Hospital, Biomolecular Laboratory of Medical Faculty, Universitas Udayana, Bali, Indonesia andProdia Laboratory Denpasar.A 12 months-period of the study was enrolled from August 1st 2016-2017. The polymorphism examination of rs2549782 ERAP 2 gene, extracellular fetal DNA content and C cystatin respectively were evaluated among 31 maternal with PE as case and 31 maternal as control (Normal). Data were analyzed using SPSS version 16 for Windowsto determine the association of rs2549782 ERAP2 genepolymorphism, extracellular fetal DNA level, and maternal serum cystatin C level using Chi-square Test and Odds Ratio (OR). Discriminant tests with logistic regression were displayed in table and narrative form.Results: The ERAP2 gene polymorphism in the case was found 7.5 times (OR = 7.50 IK95%: 3.53-15.92; p = 0.002) higher significantly compared to the control. The cell-free fetal (cff) DNAlevel in the case was 6.67 times (OR, 6.67 IK; 95% 2.67-26.33, p; 0.001) higher significantly than the control. In addition, the level of cystatin C in the case was also 6.5 times (OR, 6.5 IK; 95% 3.04-13, 89, p; 0.007) higher significantly when compared to the control. However, there wasno significant difference in the polymorphism of rs2549782 ERAP2 gene, extracellular fetal DNA, and cystatin C between groups (P>0.05).Conclusion: In can be concluded that the polymorphism of rs2549782 ERAP2 gene, extracellular fetal DNA, and high maternal serum C cystatin increase the risk of PE.Keywords:Preeclampsia, Rs2549782 polymorphism, ERAP2, DNA, cystatin C.